The LifeWebs project: A call for data describing plant-herbivore interaction networks - Tom Maurice Fayle; Katerina Sam; Anna Humlova; Luciano Cagnolo; Vojtech Novotny (Frontiers of Biogeography)
Understanding global drivers of changes in species interactions is vital, both in terms of improving our knowledge of fundamental large-scale ecology, and in order to predict and protect against human-driven changes to ecosystems. Here we present the LifeWebs project, which aims to collate existing data on interaction networks in order to understand their large-scale patterns. Initially we will collate data relating to plant–herbivore interactions, and this article is a call for contributions. We outline the kinds of data in which we are interested, the procedure for making contributions, and what contributors can expect in terms of co-authorship on subsequent papers and access to the database for conducting their own analyses.